The Role of Jawhar Nameq Salim in Preparation and Occurrence the Kurdish May Opposition 1975-1976 - Tatar Tufeeq, Ali; Hussein Sheenk, Shwan (Journal of Duhok University, 2019)
A group of Peshmerga of the September Kurdish Revolution in Kurdistan of Iraq (1961-1975) had to sought refuge in Iran with the leadership of the revolution following the setback of the September Revolution, as the result of an international conspiracy sponsored by Algeria on March 6, 1975 between Mohammad Reza Sha of Iran (1919-1980) and Saddam Hussein Vice-President of Iraq republic. While some other of them sought refuge in Syria, where a number of advanced members of the Kurdistan Democratic Party (Parti) and under the supervision of Idris Barzani (1944-1987) and Massoud Barzani, the sons of the Kurdish revolution leader Mulla Mustafa Barzani (1903-1979). A few weeks after the setback, a group of the experienced members and Peshmerga were sent to Kurdistan of Iraq in order to prepare to ignite the revolution again.Jawhar Namiq Salem (1946-2011) and Karim Sinjari, as well as a number of other members and peshmerga, were among the first to arrive in Kurdistan of Turkey at the end of 1975, where they managed despite the difficult and dangerous conditions and the surveillance of the SAVAK (the Iranian National Intelligence and Security Organization). In addition to Iraqi forces on the Iraqi-Turkish-Iranian border, that were positioned in the border villages of these countries.The Kurds in Kurdistan of Turkey, played an important role in helping the outbreak of the revolution, the efforts and the struggle of Jawhar Namiq and his colleagues the (Parti) organizations in the region of Badinan (almost the current province of Dohuk) managed to reorganize, and prepare several detachments from the Peshmerga after securing and preparing weapons, At the end of May and early June 1976, the armed struggle in Badinan against the Iraqi government began.